Cefazolin Improves Anesthesia and Surgery-Induced Cognitive Impairments by Modulating Blood-Brain Barrier Function, Gut Bacteria and Short Chain Fatty Acids - Luo, Ailin; Li, Shan; Wang, Xuan; Xie, Zheng; Li, Shiyong; Hua, Dongyu (Frontiers in Aging Neuroscience, 2021)
Emerging evidence suggests that anesthesia and surgery may induce gut dysbiosis. Gut dysbiosis leads to imbalance in circulating contents of microbiota-derived metabolites and disrupts the integrity of the blood-brain barrier (BBB), contributing to postoperative cognitive dysfunction (POCD). The composition of gut microbiota may be influenced by various antibiotics. However, how perioperative use of antibiotics affects POCD needs more explorations. In the present study, we explored the effect of cefazolin, a common antibiotic used in perioperative period, on cognitive function, BBB integrity, gut bacteria and short chain fatty acids (SCFAs), a group of widely studied metabolites in aged mice, using 18-month-old male mice. Significant BBB disruptions and decreased levels of tight junction proteins, zonula occludens-1 (ZO-1) and Occludin (OCLN) were seen in the mice of POCD model. Cefazolin treatment attenuated these changes induced by anesthesia and surgery. Furthermore, cefazolin reversed the changes in several fecal bacteria (β-, γ/δ-, ε-Proteobacteria and Bacteroidetes) as determined by qPCR tests. Analysis of plasma SCFAs showed that almost all types of SCFAs were reduced in POCD and cefazolin administration reversed the changes in expression of the two most abundant SCFAs (acetic and propionic acids). In conclusion, this study demonstrated that cefazolin improved POCD. Mechanistically, cefazolin suppressed the disruption of BBB, gut microbiota or SCFAs, thereby ameliorating POCD.